Investigation Of Ground Temperature For Heat Sink Application In Kuching, Sarawak, Malaysia - Imran S., Muhammad; Baharun, A.; Halipah S., Ibrahim; Wan A., Wan Z.B. (JCECT, 2016)
Ground Air Heat Exchanger (GAHE) may be a solution to improve thermal comfort in buildings located in Sarawak but no ground survey specifically to examine the potential of GAHE has been done. Ground temperature prediction with computer program did not provide an accurate result for this region. In this study, a few sites with different soil profile in Kuching, Sarawak were selected to determine the soil temperature up to 4 meters depth. For peat soil area with high water table, the ground mean temperature is about 28 °C after 1m depth. For sandy clay type soil which is subjected to tidal activity, the daily soil temperature fluctuates greatly with the highest maximum temperature exceeding 32°C for all depth. This behavior is not really desirable if the ground were to be used as a steady heat sink source. Red podzolic soil gave an almost flat profile between 26°C to 27°C after the depth of 1m which is more desirable as a ground heat sink source. Therefore earth tube application in the state of Sarawak should consider the type of soil profile and optimum depth of to take advantage of the cool ground to provide building cooling.